Role of the Cingulate Cortex in Dyskinesias-Reduced-Self-Awareness: An fMRI Study on Parkinson’s Disease Patients - Palermo, Sara; Lopiano, Leonardo; Morese, Rosalba; Zibetti, Maurizio; Romagnolo, Alberto; Stanziano, Mario; Rizzone, Mario Giorgio; Geminiani, Giuliano Carlo; Valentini, Maria Consuelo; Amanzio, Martina (Frontiers in Psychology, 2018)
Objectives: The detection of dyskinesias-reduced-self-awareness (DRSA) in Parkinson’s disease (PD) was previously associated to executive and metacognitive deficits mainly due to dopaminergic overstimulation of mesocorticolimbic circuits. Response-inhibition dysfunction is often observed in PD. Apart from being engaged in response-inhibition tasks, the anterior cingulate cortex (ACC) is part of a functional system based on self-awareness and engaged across cognitive, affective and behavioral contexts. The purpose of the study was to examine the relationship between response-inhibition disabilities and DRSA using whole-brain event-related functional magnetic resonance imaging (fMRI) over the course of a specific executive task. Methods: Twenty-seven cognitively preserved idiopathic PD patients - presenting motor fluctuations and dyskinesias - were studied. They underwent a neurological and neuropsychological evaluation. The presence of DRSA was assessed using the Dyskinesias Subtracted-Index (DS-I). Cingulate functionality was evaluated with fMRI, while patients performed an ACC-sensitive GO-NoGO task. Association between blood oxygenation level dependent response over the whole-brain during the response-inhibition task and DS-I scores was investigated by regression analysis. Results: The presence of DRSA was associated with reduced functional recruitment in the bilateral ACC, bilateral anterior insular cortex and right dorsolateral prefrontal cortex (pFWE<.05). Moreover, DS-I scores significantly correlated with percent errors on the NoGO condition (r=.491, pFWE=.009). Discussion: These preliminary findings add evidence to the relevant role of executive dysfunctions in DRSA pathogenesis beyond the effects of chronic dopaminergic treatment, with a key leading role played by ACC as part of a functionally impaired response-inhibition network. Imaging biomarkers for DRSA are important to be studied, especially when the neuropsychological assessment seems to be normal.